Molecular Mechanisms Controlling the Differentiation of Germ Cells in mammals: Divergent expression patterns of SLBP in male and female meiotic cells and their developmental consequences - Martin, Kyle J.; Clarke, Hugh J. (McGill Science Undergraduate Research Journal, 2006)
The stem-loop binding protein (SLBP) binds to replication-dependent histone mRNA and participates in its processing, stabilization and translation. It has previously been shown that SLBP expression in somatic cells is regulated by the cell cycle. Our work demonstrates that male and female germ line cell expression patterns differ dramatically both from the somatic cell-cycle regulated pattern, and from each other. Using immunofluorescence on a post-natal series of male and female gonads, SLBP was shown to translocate from the cytoplasm of non-growing oocytes to the nucleus upon initiation of growth, followed by re-entry into the cytoplasm upon entry into metaphase II. In contrast, developing male germ cells initially express SLBP at high levels both in the nucleus and the cytoplasm, followed by cytoplasmic segregation and finally complete absence of expression by maturation. We believe that these divergent expression patterns in male and female germ cells reflect the different requirements for SLBP in cell differentiation and early embryogenesis, respectively.